STUDI LITERATUR:HUBUNGAN PERSONAL HYGIENE DENGAN KEJADIAN SKABIES DI PONDOK PESANTREN - Zairina Audini Siagian (Jurnal Kesehatan, 2024)
Scabies is an infectious skin disease caused by the parasite Sarcoptes scarbiei var. Hominis is caused by a specific human ectoparasite with a size of about 0.4 mm, which is invisible to the naked eye. This study aims to find out how personal hygiene is related to the incidence of scabies in Islamic boarding schools. This research uses the Rivew literature study method, where researchers search for, combine and analyze essences from various scientific sources that are accurate and valid. The data source used in this research is the Google Scholar website, and select articles and journals with the researcher's title using these keywords. The literature used is articles published between 2018 and 2022. Research results from various professional journals have found a relationship between personal hygiene and the occurrence of scabies. This happens because there is no health education about scabies, the causes of scabies, prevention or even treatment of scabies, apart from that the occurrence of scabies is influenced by the behavior of students regarding personal hygiene, about how to maintain personal hygiene.